Peranan Media Sosial terhadap Kenaikan Nilai Omset Penjualan di "Tiktok" pada Pedagang dengan Cara Live Shopping - Handy Aribowo; Erlina Erlina (Jurnal Mirai Management, 2023)
This research utilizes a qualitative descriptive research method. Data will be collected through literature review, observation, and interviews with merchants who use live shopping on TikTok. Data analysis will be conducted using an inductive and qualitative approach. This research underscores the role of social media, particularly TikTok, in enhancing sales revenue for merchants through live shopping. In this study, it was found that TikTok provides significant support for merchants in reaching a broader audience, expanding the reach of products, and engaging directly with potential consumers. This support includes the live shopping feature that combines real-time streaming with purchase transactions, allowing for direct product introductions to the audience and facilitating quick and easy transactions. Furthermore, TikTok also offers features and support such as business accounts, promotion assistants, ad support, live streaming, popular campaign content support, data analytics, Shopping Center Analytics, and TikTok Shop Academy. These supports help merchants increase brand exposure, build customer relationships, and ultimately boost sales and revenue. Through the combination of these features and support, TikTok provides merchants with the opportunity to maximize the potential of the platform and achieve success in their businesses. This research concludes that the role of social media, especially TikTok, in live shopping is highly significant in enhancing sales revenue for merchants. Keywords: Tiktok, Live Shopping, Omset, Media Sosial